In and out of the mind in Greek tragedy - Padel, R; Padel, Ruth Sofia (1976)
﻿ The purpose of this thesis has been to use tragedy to discover conceptions about mental and emotional processes reflected in contemporary language which, though it may not have been used throughout the society in the particular forms tragedy uses, was understood, and felt to be powerful, by the contemporary audiences of the plays. Through detailed examination of the type of imagery used in thinking about the mind, various inferences have been made about conceptions of the sources of harmful emotion and about the ways in which men judge each other, how they sympathize with each other, and how far they can understand each other's private feelings, in a society which may have been in these respects very different from our own. The material has been confined to tragedy - though parallels from other poets and evidence of particular beliefs and theories have been sought in archaeological data, medicine, philosophy and history - since tragedy, is for two reasons, particularly suitable for a study of this kind. First, the process of watching a tragedy involves observation aid evaluation of other people from their actions; the audience is invited to react to and ponder the implications of different 'serious actions' the imitation of which is included in Aristotle's definition of tragedy. Secondly, tragedy is a musical event which offers in different musical patterns the expression and resolution of extreme emotions; and one of the main points to emerge in this thesis is Greek fears of unrhythmical and uncontrollable emotion. The images associated with emotion are those of savage daemons and wild beasts. As on the mythological level Orpheus could control wild beasts by the power of his music, on the social and dramatic level music, which imposes order, rhythm and harmony on those listening to it and performing it, can calm extreme emotions in ritual and in tragedy, of which it is an essential part. Chapter One: In the Mind. This chapter examines statements about the composition of the mind in tragedy: the different mental organs, located deep within the hitman body, their movement in relation to each other, and their 'darkness'. The images which express the activity of the mind disturbed include: shaking and trembling, filling, swelling and inflammation; wave, storms, wind and breath. The dreams that visit the mind are imagined as coming out of the earth; but the 'muchos' of the mind is implcitly compared to the underground darkness in which the blind seer lives. The mind itself is imagined to be 'prophetic'. The imagery of wave and storm, drawn from the world outside to express feelings within the mind, suggests the easy association of the components of the natural world and the components of the mind; an association demonstrated in the theories of Presocratics and Hippocratic writers. Finally, the supreme fear is fear of the mind 'adrift': the motif of the 'wandering mind' is reflected in the geographical wandering of mad figures in myth. Their activities and feelings are expressed in images and pursuit: of the goad, yoke, and whip. Chapter Two: Into the Mind. This chapter explores the outside sources of mental harm. Passions that trouble the mind are expressed and described with the help of imagery, and the imagery draws mainly on the outside world: on the daemons of cult and fantasy, and on the wild animals who endanger man physically. Part A considers the shapes of persecution, culturally-determined, which provide models for the individual imagination. The Olympian gods, their winged weapons; the Erinyes, their goads and love of blood; the Gorgon, her piercing eye; the Sphinx, her claws and dangerous song; the animals, the 'death-bringers', particularly the bull, horse, dog, lion and snake. Part B examines the images of emotion themselves: wings and piercing weapons; rays of the eye; driving and blows; hunting and ambush; wrestling and capture (human imagery); biting and eating (animal imagery); and imagery from the natural world, wind, wave, fire, storm. Chapter Three: Into And Out Of The Mind. The material studied so far suggests a world-view which emphasizes the external source of human emotion and pain. But some images, some forms of theory, some direct atatements in tragedy (and elsewhere at this period) suggests that another world-view also operated within the imagination; that the source of human emotion and disease lay within man himself. For various reasons, not least emotional comfort, this view is not canvassed as widely, nor does it affect language and belief as powerfully, as the first. There are areas of experience, however, where it is important, and particularly in ideas about madness and demonic possession. Madness in tragedy is presented as a temporary event which passes and leaves the man 'himself' again. The case for belief in demonic possession at this period, which has been challenged recently, is reconsidered; and the implications of demonic possession and inspiration are discussed, of the external and internal sources of power good and bad. Examples are collected of the recognition in tragedy of the projection process, lay which the mind projects its own feelings, particularly the dangerous ones, outside into the world. The psychoanalytic concept of projection is outlined, and the role it has played in psychologically-oriented medical history: particularly in Paracelsus and Freud. Fifth-century medical theories are examined: theories of the origin of the physical and mental disease. These invoke both external sources of harm, and internal ones. In medicine and poetry alike the two views, though apparently paradoxical, operate in a complementary way, since belief is shifting and inconstant in societies and individuals alike. There are parallels in Anthropological material for the complementary relation of inconsistent world views: and the tendency of theorists has always been to divide mental functioning into two types (compare theories which divide mental structures, and divide them into three). Chapter Four: Out Of The Mind. This chapter considers the actions that express emotion. These are of two kinds, the individual actions of which tragedy is composed (considered in chapter five), and involuntary and ritualized actions, which may have sons universal physiological basis but which are also culturally determined. The natural process of observation - 'opsis' - is replaced in tragedy by words (eg 'Why are you pale?'). Physical reactions to emotion mentioned in tragedy are collected, and deductions made by observers about the internal feelings which produce such reactions. Parallels from medicine are considered: the importance of observation in medical theory and practice has given us a picture of the physical symptoms of physical disease which resemble the physical symptoms of emotion recorded in tragedy. There are dangers in taking physical symptoms recorded in poetry too literally (illustrated by a study of Sappho fr. 31), but though the poetic expression of such symptoms is affected by dictates of convention and genre, it does provide evidence for the tendencies of observation and reaction accepted in the whole society, if not for the single 'true' experience of a lyric poet. Tragedy: the main feature in physical symptoms of emotion and madness is a terrifying unrhythmical violence, which corresponds to the wild movements of the pursuing daemons in Chapter two, and the wild twisting movements in the images of the mind of Chapter one. The principle of projection, discussed in Chapter three, is working here, projecting the wild movements of the body of the man suffering intense emotions, onto both his imagined pursuers, and the unseen organs of his mind. Ritualized expression of emotion is an attempt to impose order, rhythm and control on this violence. The ritual expression of grief, the emotion which occurs most often in tragedy, tries to control emotion in two ways. First, by identification of the mourner with the dead man; shown symbolically by the veiled head, self-mutilation, black robes, and conventional expressions which involve refusal of the normal activity and perceptions of living men. This endangers the individual; he or she is isolated, as the madman (wandering away from civilization, chapter one) is isolated, and as the tragic hero (in chapter five) is isolated in his unique sufferings from the people around him. So the second aim of the mourning-ritual as depicted in tragedy is the identification of the mourner with the group: mourning with someone is a gift, which draws the isolated mourner back into the community. This is achieved partly through the imposition of rhythm and harmony on the expressions of pain. 'Harmonia' is a musical concept which is used elsewhere in ethics and politics for instance and for individual peace of mind: the relation of the individual with the group is an important element in most areas of Greex thought. Mp>Chapter Five: Out Of The Mind. This chapter concentrates on the ways available to the contemporary audience of judging the people they observed acting on the stage. The metaphor of the mirror, which is both self-revealing and other-revealing is used first in its other-revealing capacity: the mirror of friendship and 'homilia', the best available way of judging another person. The Greek love of typology in considering human characters (first shown in Semonides of Amorgos), is demonstrated in two ways in tragedy: first, at the simple physical level (status, sex, age) marked by the masks of tragedy. Secondly, by the use of moral advertisement: gnomai. An early example is given of the use of gnomai as moral advertisement: Odysseus and Aloinous in Od. 7. Tragedy: examples of the 'moral mask' in self-introduction, observation and judgement: from A. Supp., 1ff; S. OC 11ff; S. Phil. 54ff. Tragic expressions of the limitation of conventional methods of judgement are linked to the conventional wish for an external mark, and to the acknowledgement that gnomai may be as empty as a physical mask. Notions of 'individuality' in the fifth century, and contemporary (and later) popular and philosophical ideas about the 'self', are always linked to contemporary ideas of friendship, on the principle of 'like to like'. Man's judgement of other people is held to be related to his conception of himself; this has a significance in fifth-century society different perhaps from that in our own, since the notion of the state, and of the state's rights over the individual, were valued more highly: the 'self -revealing' mirror is linked to the 'other revealing' mirror. Tragic action does at one level reveal character. An individual is judged as responsible in human terms for his actions, though recognition of the incalculable effect of the divine world on the human mind is a constant factor in reactions to other people, in tragedy as in life. Conclusion. Tragedy shows that man's mind is felt to be as vulnerable to emotions and non-rational forces, experienced for the most part as external pressures, as his body is to the elements and animals of the physical world. All men are alike in this; through their observation of particular actions (and the possible emotion deducible both from the action and from the language of tragedy), each member of the audience could consider the universal vulnerability of man to external fate. However, it was also possible to suppose that passions arose within the individual; at this level, it was possible for one man to judge another, through observation of his actions. The experience of watching a tragedy involved identification with the sufferer, through acknowledgement of the universal vulnerability of man; but it also involved an objective perception of him, a decision 'like me therefore not me'. At this level the tragic hero functioned as a particular example, which could be judged by the culturally-acquired processes of judging another human being current in the contemporary society. Identi- fication with the hero produced the terror; objective observation of him produced the pity. But these emotions were pleasurable, not harmful, to the audience since they were contained within the safe rhythm and 'harmonia' of tragedy.